Model Pemberdayaan Masyarakat Desa Tangguh Bencana Berbasis Pendidikan Interprofesional dan Kearifan Lokal - Hupitoyo, Hupitoyo; Sumasto, Hery Sumasto; Rahayu, Teta Puji Rahayu; Suparji, Suparji; Wisnu, Nurwening Tyas Wisnu; Widyawati , Widyawati (Health Community Engagement, 2024)
Ngiliran Village, Panekan District, Magetan Regency, is an area that has a high level of vulnerability to natural disasters such as landslides and the threat of non-natural disasters such as the Covid-19 pandemic. This community service aims to empower the people of Ngiliran Village in increasing disaster preparedness and mitigation capacity through an interprofessional collaborative approach and the use of local wisdom. Activities include classical training, disaster simulations at the village and school levels, the preparation of participatory data-based risk maps, and trauma healing through cultural arts and traditional games. The results of the activity showed an increase in community knowledge and skills in various aspects of disaster mitigation by more than 50%, the formation of a Disaster Resilient Village Task Force consisting of various elements of the community, as well as a positive response to trauma healing that succeeded in restoring the psychosocial condition of residents. Research-based approaches, cross-professional collaboration, and community empowerment have proven effective in creating Ngiliran Village that is resilient to disasters in a sustainable manner. Follow-up studies are recommended to measure the sustainability of the impact of these interventions, as well as the integration of information technology in disaster risk management